Sistem Pakar Diagnosa Fobia Menggunakan Metode Certainty Factor - Gita Prastianingrum; Agus Sidiq Purnomo (LPPM Universitas Mercu Buana Yogyakarta, 2019)
Someone who reacts with extreme fear in a stimulus or situation which according to most others is not very dangerous, is called a person who has a phobia. As parents we should be vigilant about the symptoms of this phobia from an early age and be able to work on how to handle it appropriately. Given this, in this study an application will be made to be able to identify someone have a phobia or not.Observation will be done through questionnaire. With each answer will have value for the symptoms of the phobia. The first stage is data collection. From 45 respondents, questionnaire data were obtained which were then processed with statistics through the system. The method used in this system is Certainty Factor. This application uses 45 data. Test effectiveness reaches results where expert test results with system test results are the same. With a percentage of 10% for patients who do not have phobias, 40% for mild risk levels, 47% for moderate risk levels, and 9% for severe risk levels. It is hoped that this research can be refined and developed as well as helping to make the application for phobia handling consultation to the entire community free of charge.